Level of menarche anxiety before and after adolescent reproductive health education in SDN 19 Lahat Students - Rosa Gunadi, Helmi; Soenggono, Arifin; Mutmaini, Silsa (ACTA Medical Health Sciences, 2024)
Women menstruate at varying ages, making it difficult for adolescent girls to describe what is going on with their bodies. They are unprepared and unable to manage their menstruation appropriately due to the limited source of information they receive. As a result, teenage girls experience anxiety symptoms such as fear, anxiety, and discomfort. Anxiety can be decreased by giving the female students sufficient education associated with reproductive health prior to menarche via video media, presentations, discussions, and questions and answers. In this study, an experimental strategy was being used, with a pre-experimental design and a pretest and posttest one-group design. Because the study was conducted on variables for which no data was available, the process had to be modified by providing particular treatments to the research subjects, which were then observed and measured. Before the intervention, it was known that 22 respondents (58%) were not anxious, 4 respondents (11%) had mild anxiety, 7 respondents (18%) had moderate anxiety, 5 respondents (13%) had severe anxiety, and there were no respondents with very severe anxiety. Following the health education intervention, it was observed that 25 respondents (66%) had no anxiety, 6 respondents (16%) had mild anxiety, 4 respondents (11%) had moderate anxiety, and 3 respondents (8%) had severe anxiety but did not report it. There were some people who were experiencing significant anxiety. The students of SD Negeri 19 Lahat experienced a significantly reduced anxi ety concerning menarche both before and after receiving reproductive health education. DOI : 10.35990/amhs.v2n3.p116-121 REFERENCES Martinez, G. M. (2020). National Health Statistics Reports, Number 146, September 10, 2020. (Original work published 1995). Retrieved from https://www.cdc.gov/nchs/products/index.htm Sinaga, E. S., & Lubis, A. (2021). Factors relating to siswi behavior class VII in facing menarche. Gentle Birth, 4(1). Sudikno, & Sandjaja. (2019). Usia menarche perempuan Indonesia semakin muda: Hasil analisis Riskesdas 2010. Jurnal Kesehatan Reproduksi, 10(2), 163–171. https://doi.org/10.22435/kespro.v10i2.2568.163-171 Sommer, M., Sutherland, C., & Chandra-Mouli, V. (2015). Putting menarche and girls into the global population health agenda. Reproductive Health, 12(1). https://doi.org/10.1186/s12978-015-0009-8 Tanton, C., Nakuya, K., Kansiime, C., et al. (2021). Menstrual characteristics, menstrual anxiety and school attendance among adolescents in Uganda: A longitudinal study. BMC Women's Health, 21(1). https://doi.org/10.1186/s12905-021-01544-6 Starrs, A. M., Ezeh, A. C., Barker, G., et al. (2018). Accelerate progress—Sexual and reproductive health and rights for all: Report of the Guttmacher–Lancet Commission. The Lancet, 391(10140), 2642–2692. https://doi.org/10.1016/S0140-6736(18)30293-9 Prijatni, I. (2013). Kesehatan reproduksi dan keluarga berencana. Badan Pengembangan dan Pemberdayaan Sumber Daya Manusia Kesehatan. Tortora, G. J., & Derrickson, B. (2018). Principles of anatomy and physiology (12th ed.). John Wiley & Sons, Inc. Sherwood, L. (2016). Human physiology: From cells to systems (9th ed.). Cengage Learning. Vismara, M., Girone, N., Cirnigliaro, G., et al. (2020). Peripheral biomarkers in DSM-5 anxiety disorders: An updated overview. Brain Sciences, 10(8), 1–37. https://doi.org/10.3390/brainsci10080564 Hermawatu, Muchtar, M., Wiwi, S., & Syarwini. (2016). Pendidikan kesehatan dalam kesiapan menghadapi menarche di sekolah dasar. Jurnal Penelitian dan Kajian Ilmiah, 10, UMSB. Herwati, Muchtar, M. (2017). Model pendidikan kesehatan terhadap pengetahuan dan sikap dalam kesiapan menghadapi menarche di sekolah dasar. Jurnal Penelitian dan Kajian Ilmiah, 11(75), UMSB. https://doi.org/10.33559/mi.v11i75.453 Mendle, J., Ryan, R. M., & McKone, K. M. (2018). Age at menarche, depression, and antisocial behavior in adulthood. Retrieved from http://www.publications.aap.org/pediatrics/articlepdf/141/1/e20171703/1066419/peds_20171703.pdf Kautsar, F., Gustopo, D., & Achmadi, F. (2017). Uji validitas dan reliabilitas Hamilton Anxiety Rating Scale terhadap kecemasan dan produktivitas pekerja visual inspection PT. Widatra Bhakti. Prosiding SENATEK, 1(A), 588–592. Kementerian Kesehatan Republik Indonesia. (2017). Pedoman dan standar etik penelitian dan pengembangan kesehatan nasional. Ningrum, M. W. P., & Purnomo, W. (2020). Relationship between readiness and anxiety level in elementary school students facing menarche in Pademawu Sub-District, Pamekasan. Jurnal Biometrika dan Kependudukan, 9(2), 95–103. https://doi.org/10.20473/jbk.v9i2.2020.95-103 Burnet Institute, Water Aid Australia, & Aliansi Remaja Independen. (2015). Menstrual hygiene management in Indonesia: Understanding practices, determinants and impacts among adolescent school girls. Retrieved from www.aliansiremajaindependen.org Lutfi, I. (2017). Analisis kesiapan siswi sekolah dasar dalam menghadapi menarche. Jurnal Bioetika dan Kependudukan, 5(2), 135–145. https://doi.org/10.20473/jbk.v5i2.2016.135-145 Emdadul Haque, S., Rahman, M., Itsuko, K., Mutahara, M., & Sakisaka, K. (2014). The effect of a school-based educational intervention on menstrual health: An intervention study among adolescent girls in Bangladesh. BMJ Open, 4, e004607. https://doi.org/10.1136/bmjopen-2013-004607 Intan, O., Hudaya, N., Gantini, D., & Patimah, S. (2019). Pengaruh pendidikan kesehatan reproduksi (Underwear Rules) terhadap pengetahuan anak prasekolah. Edutech: Jurnal Teknologi Pendidikan, 18(3). https://doi.org/10.17509/e.v18i3.18071